Influenza B Pneumonia with Pneumomediastinum, Subcutaneous Emphysema and Encephalitis. A Rare Presentation - Prachi Singh; Ankit Pachauri (National Board of Examinations Journal of Medical Sciences)
Children under the age of five are more vulnerable to influenza because they are an immunologically naïve population. When treating a child with viral pneumonia, severe consequences after an influenza infection must be considered. Here we are reporting a case series of 2 atypical severe influenza B pneumonia cases in children complicated with necrotising pneumonia, pneumothorax, and encephalitis.